Symmetries, integrating factors and Nambu mechanics - G., Ünal (Elsevier BV, 1996)
zbMATH Open Web Interface contents unavailable due to conflicting licenses.
Keywords: General models, approaches, and methods in mechanics of particles and systems; Symmetries, invariants, invariant manifolds, momentum maps, reduction